Taxonomy, biology and cytology of four species of Stigeoclonium (Chaetophorales, Chlorophyceae) from Argentina - Michetti, Karina Mariel (2010)
Four species of Stigeoclonium from Argentina were studied by means of transmission electron microscopy and light microscopy. For species identification, we collected data related to the prostrate system and zoospore germination. We also determined the chromosome number for each species. Stigeoclonium aestivale showed a more developed erect system than the prostrate one, zoospore germination was predominantly of erect type and the chromosome number was 8. Stigeoclonium tenue presented well developed, erect and prostrate systems, zoospore germination was initially of the prostrate type and the chromosome number was 5. In Stigeoclonium variabile the prostrate system predominated over the erect one, zoospore germination was strictly of the prostrate type and the chromosome number was 3. Stigeoclonium farctum presented a more developed prostrate system than the erect one, zoospore germination was strictly of the prostrate type and the chromosome number was 8. The ontogeny of the zoospore germination was related to the final relative development of the prostrate and erect portions of adult thalli.